Can the crowdsourcing data paradigm take atmospheric science to a new level? A case study of the urban heat island of London quantified using Netatmo weather stations. (2nd December 2016) - Chapman, Lee; Bell, Cassandra; Bell, Simon
ABSTRACT: Crowdsourcing techniques are frequently used across science to supplement traditional means of data collection. Although atmospheric science has so far been slow to harness the technology, developments have now reached the point where the benefits of the approaches simply cannot be ignored: crowdsourcing has potentially far‐reaching consequences for the way in which measurements are collected and used in the discipline. To illustrate this point, this paper uses air temperature data from the prolific, low‐cost, Netatmo weather station to quantify the urban heat island of London over the summer of 2015. The results are broadly comparable with previous studies, and indeed standard observations (albeit with a warm bias, a likely consequence of non‐standard site exposure), showing a range of magnitudes of between 1 and 6 °C across the city depending on atmospheric stability. However, not all the results can be easily explained by physical processes and therefore highlight quality issues with crowdsourced data that need to be resolved. This paper aims to kickstart a step‐change in the use of crowdsourcing in urban meteorology by encouraging atmospheric scientists to more positively engage with the new generation of manufacturers producing mass market sensors.